Hyperelastic properties of bamboo fiber-reinforced silicone rubber biocomposites via compression test - Kamarul Bahrain, Siti Humairah; Che Abd Rahim, Nor Nabilah; Mahmud, Jamaluddin; Mohammed, M. N.; Salit, M. Sapuan; R. A., Ilyas; Alkhatib, Samah Elsayed; M. Asyraf, M. R. (Multidisciplinary Digital Publishing Institute, 2022)
Materials that exhibit highly nonlinear behaviour are intricate to study. This is due to their physical properties, as they possess a very large deformation. Silicone rubber is among the materials that can be classified as possessing such characteristics, despite their being soft and frequently applied in medical applications. Due to their low mechanical properties, however, it is believed that a filler addition could enhance them. This study, therefore, aims to investigate the effect of the addition of bamboo cellulosic filler to silicone rubber in terms of its compressive properties in order to quantify its material constants using the hyperelastic theory, specifically the Neo-Hookean and Mooney–Rivlin models. The specimens’ compressive properties were also compared between specimens immersed in seawater and those not immersed in seawater. The findings showed that the compressive properties, stiffness, and compressive strength of the bamboo cellulosic fibre reinforced the silicone rubber biocomposites, improved with higher bamboo filler addition. Specimens immersed in seawater showed that they can withstand a compressive load of up to 83.16 kPa in comparison to specimens not immersed in seawater (up to 79.8 kPa). Using the hyperelastic constitutive models, the Mooney–Rivlin model displayed the most accurate performance curve fit with the experimental compression data with an R2 of up to 0.9999. The material constant values also revealed that the specimens immersed in seawater improved in stiffness property, as the C1 material constant values are higher than for the specimens not immersed in seawater. From these findings, this study has shown that bamboo cellulosic filler added into silicone rubber enhances the material’s compressive properties and that the rubber further improves with immersion in seawater. Thus, these findings contribute significantly towards knowledge of bamboo cellulosic fibre–reinforced silicone rubber biocomposite materials.